Optimal Debt Structure and the Number of Creditors - Bolton, Patrick; Scharfstein, David S. (Journal of Political Economy, 1996)
Within an optimal contracting framework, we analyze the optimal number of creditors a company borrows from. We also analyze the optimal allocation of security interests among creditors and intercreditor voting rules that govern renegotiation of debt contracts. The key to our analysis is the idea that these aspects of the debt structure affect the outcome of debt renegotiation following a default. Debt structures that lead to inefficient renegotiation are beneficial in that they deter default, but they are also costly if default is beyond a manager's control. The optimal debt structure balances these effects. We characterize how the optimal debt structure depends on firm characteristics such as its technology, its credit rating, and the market for its assets.